2022
DOI: 10.1001/jamanetworkopen.2022.35984
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safe Firearm Storage Messaging in a Sample of Firearm-Owning US Military Service Members

Abstract: ImportanceNearly two-thirds of military suicides involve firearms, and safe firearm storage is rare.ObjectiveTo examine whether US military service members endorse greater openness to safe firearm storage depending on the content of the visual message they are randomly assigned to view.Design, Setting, and ParticipantsThis comparative effectiveness study used a 3 × 2 × 2 factorial design to randomize US military service members to view 1 of 12 visual messages on safe firearm storage. Willingness to use safe fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
(38 reference statements)
3
17
0
Order By: Relevance
“…This may indicate firearm owners perceive risks associated with child access as outweighing the risk of potential home invasion. Secure firearm storage messaging that helps clarify the risk of unsecured firearms beyond situations involving child access may thus serve as a method for increasing secure storage; however, such messaging must rely on credible sources who deliver their messages via trusted channels …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate firearm owners perceive risks associated with child access as outweighing the risk of potential home invasion. Secure firearm storage messaging that helps clarify the risk of unsecured firearms beyond situations involving child access may thus serve as a method for increasing secure storage; however, such messaging must rely on credible sources who deliver their messages via trusted channels …”
Section: Discussionmentioning
confidence: 99%
“…Secure firearm storage messaging that helps clarify the risk of unsecured firearms beyond situations involving child access may thus serve as a method for increasing secure storage 17 ; however, such messaging must rely on credible sources who deliver their messages via trusted channels. [21][22][23]…”
Section: Jama Network Open | Public Healthmentioning
confidence: 99%
“…They found that, among parents who were offered the devices, fewer took and used cable locks (14%) than handgun lockboxes (28%). In the study by Anestis et al, among respondents using a locking device, gun safes were commonly reported to be used regardless of the reason for firearm ownership or specific locking mechanism (keypad/personal identification number/dial vs biometric). There were, however, more notable differences in the choice of locking devices between those who owned handguns only and those who owned long guns only.…”
mentioning
confidence: 95%
“…However, our knowledge of precise storage practices, and in particular variations and preferences in using different firearm-locking devices, remains limited. Anestis et al present findings of a nationally representative survey among firearm owners in 2022 to characterize firearm storage practices, locking device preferences, and circumstances that would encourage locking unsecured firearms. They find that 58.3% of the sample reported storing at least 1 firearm unlocked and hidden, and 17.9% reported storing at least 1 firearm unlocked and unhidden.…”
mentioning
confidence: 99%
See 1 more Smart Citation